(untitled) (Tanzania Medical Journal, 2022)
Background Esophageal cancer is a serious malignancy with regards to its associated morbidity of inability to swallow and the grave prognosis. Coordinated care, including multidisciplinary approach has the potential to impact outlook for these patients. This requires adequate staging, addressing nutritional and performance status, and treatment stratification in a more objective manner. Marked with low resection rates, the management practices at our hospital have not been highlighted. This would identify snags and allow addressing improvements and overall patient’s outcome. Aim To determine if EC patients are adequately investigated, staged and optimized prior to any form of cancer targeted treatment and discuss opportunities to optimize care. Methodology A retrospective, descriptive hospital based study that included all histologically conformed cases of esophageal cancer diagnosed between 2017 and 2018 at Muhimbili National Hospital. We identified medical records for 251 patients. Using data abstraction forms, patient’s demography, diagnostic and staging investigations, and the planned or offered optimization and cancer related treatment identified. Additional tumor characteristics like location, and grade was collected. Descriptive statistics were summarized into tables and figures using SPSS version 26 and MS Excel for windows for figures. Results Almost all patients with esophageal cancer had an endoscopy and biopsy done. Few patients had esophagograms and adequate staging investigations done as was in 20% and 23.5% respectively. None of the patients had nutritional assessment or performance status documented. Majority of the patients (72.4%) were planned for palliative therapy with radiation therapy. Only about 10% of the patients had esophagectomy done with low adjuvant therapy rates. Conclusion and recommendation We found lack of coordinated approach towards patients presenting with esophageal cancer. Improved staging investigations and functional status assessment would allow patients optimization and appropriate treatment stratification. The hospital needs to explore all its locally available resources towards improving the treatment landscape of patients with esophageal cancer.